Comparison of distraction techniques using salivary biomarkers during local anaesthesia administration in children aged 3-5 years: A clinical study - Yanina Singh; Poornima Parameshwarappa; Mebin George Mathew; S B Meghana; Mallikarjuna Kenchappa; N B Nagaveni (Wolters Kluwer Medknow Publications, 2023)
Aim: In paediatric dentistry, pain is adversely influenced by a child's level of anxiety. Ironically, the most common form of pain control used in dentistry, local anaesthesia, can itself produce anxiety. One of the techniques to overcome a child's anxiety is using distraction. The aim of the present study was to evaluate the effectiveness of distraction techniques, i.e. audio distraction (AD) and audio-visual distraction (AVD) by measuring salivary stress biomarker (salivary cortisol and salivary alpha-amylase) levels in 3-5 year-old children. Materials and Methods: Forty children aged 3-5 years were divided randomly into two groups; (Group I = AD, Group II = AVD). Cotton pellets were placed in the lingual vestibule to collect a sample of saliva. Children were then asked to wear overhead phones in the AD group, connected to a phone, and rhymes were played. In AVD, a cartoon movie was shown to the children using AV glasses. Simultaneously, local anaesthesia was administrated to children, after which another saliva sample was collected. Biomarker estimation was done using ELISA. Fisher's exact test was used for statistical analysis. Results: Statistically significant results were seen with Group II compared to Group I (cortisol-P = 0.009; salivary alpha-amylase-P = 0.03). Conclusion: Both distraction techniques are effective in reducing stress but compared to AD, AVD is more efficacious.